ChemInform Abstract: Catalytic Enantioselective Quick Route to Aldol‐Tethered 1, 6‐ and 1, 7‐Enynes from ω‐Unsaturated Aldehydes. Issue 17 (April 2015) - Garcia, Jesus M.; Odriozola, Jose M.; Razkin, Jesus; Lapuerta, Irati; Odriozola, Amaiur; Urruzuno, Inaki; Vera, Silvia; Oiarbide, Mikel; Palomo, Claudio
Abstract Direct cross‐aldol reaction between ω‐unsaturated aldehydes and propargylic aldehydes is developed to yield functionalized 1, 6‐ and 1, 7‐enynes and the conversion of these products to bicyclic cyclopentenone derivatives by Pauson—Khand reaction is demonstrated.